(3GdeMce aj GddZIs - (3Ydj Hf ESeGYjd, GdeYQha H` GHf SjOg, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3HGH GdKdGKi GdcGa hGdLje hGdSjf GdchSL s
(3BNQgG (B:s
(3jfJgi CKfGA GdMGA hGdQGA hGdjGA Hbhdg (B: (3bGd UNQ GdZi jUa SjakG adhf Yfg Sjha CQjM EP HGA Hcai ade CcO CLO s
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B263 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B36s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
Keywords: (3GddZIs